Assessment of Olfactory Memory in Olfactory Dysfunction. (March 2017) - Kollndorfer, Kathrin; Reichert, Johanna; Braunsteiner, Josephine; Schöpf, Veronika
To assess all clinically relevant components of olfactory perception, examinations for olfactory sensitivity, discrimination, and identification are performed. Besides the standard perceptual test battery, episodic olfactory memory might offer additional information about olfactory abilities relative to these standard clinical tests. As both olfactory deficits and memory deficits are early symptoms in neurodegenerative disorders, olfactory memory may be of particular interest. However, to date little is known about episodic olfactory memory performance in patients with decreased olfactory function. This study includes the investigation of olfactory memory performance in 14 hyposmic patients (8 female, mean age 52.6 years) completing two episodic odor memory tests (Sniffin' Test of Odor Memory and Odor Memory Test). To control for a general impairment in memory function, a verbal and a figural memory test were carried out. A regression model with multiple predictors was calculated for both odor memory tests separately. Odor identification was identified as the only significant predictor for both odor memory tasks. From our results, we conclude that currently available olfactory memory tests are highly influenced by odor identification abilities, implying the need for the development and validation of additional tests in this field which could serve as additional olfactory perception variables for clinical assessment.